Multi-actor support received by children for physical activity : hearing children’s voices - Leino, Henna M.; Ahokas, Ira; Hurmerinta, Leila; Husu, Pauliina; Kokko, Sami; Saarimaa, Riikka; Sandberg, Birgitta; Tapio, Petri; Vasankari, Tommi; Villberg, Jari; Vähä-Ypyä, Henri (Sage, 2026)
Aims:
Receiving or lacking support can be decisive in how children engage in and continue with sports hobbies or physical activity (PA) in general. The topic is timely, since the PA levels of children are currently insufficient. However, children’s own experiences concerning the support they receive are under-researched. The purpose of this study is to explore from whom, to what extent and what kind of support children experience receiving for PA.
Methods:
This mixed-methods study collected empirical data among 11-year-old children, regarding children’s own perceptions of PA by local interviews (n = 36) as the main primary material, complemented with a local survey (n = 114), and national survey (n = 1765) conducted in Finland. In addition, access to the local respondents’ accelerometer measurements conducted in five schools in a city in Southern Finland was utilised to characterise the interviewees in terms of their PA. The various data were gathered in 2021 and 2022.
Results:
According to data from both local and national surveys, children experience receiving support for PA from multiple actors (particularly from parents, teachers, hobby instructors/coaches, friends). Support styles vary from coercive to enabling, encouraging and participatory support. The combination of support from different actors can be reinforcing, remedial or destructive, depending on the type and amount of support and a child’s experiences regarding the support.
Conclusions:
To reinforce positive support experiences and to avoid destructive support combinations, shared responsibility and congruence regarding the provision of support for children’s PA is called for.